A CONTRIBUTION TO THE GENUS RODOLIA MULSANT, 1850 (CO LEOPTERA: COCCINELLIDAE) FRO M POTHWAR PLATEAU OF PAKISTAN - Z. Iqbal; M. F. Nasir; I. Bodlah; R. Qureshi (Journal of Animal and Plant Sciences, 2018)
Genus Rodolia Mulsant, 1850 (Coleoptera: Coccinellidae) mostly associated with the species of scale insects and mealybugs. A total of two species i.e. Rodolia fumida and R. octoguttata were studied from Pothwar Plateau, Pakistan during 2015-2017. R. octoguttata is recorded for the first time from Pakistan. Both of the species have been found as predator of Drosicha mangiferae (Mango mealybug) and collected from six host plants viz. Lagerstroemia indica, Mangiferae indica, Eriobotrya japonica, Alstonia scholaris, Prunus persica and Dalbergia sissoo. Information about host plants, prey, distribution, diagnostic characters and their illustrations have been provided. This information will helpful in identification of these species and their possible utilization in IPM of Mango mealybug and future research. the family Coccinellidae proposed by ZlipiDski ( 2007),
Keywords: NA